(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
The study was carried out in the period from July 2020 to August 2021, with the intention of studying the qualitative composition of the fish fauna in the Belloran Dam lake. 4families were recorded: Cyprinidae, Mugilidae, Claridae, and Cichlidae, which included 5 genera,Carssus, Cyprinus, Clarias,Liza and Tilapia has 5 species of fish: Tilapia zillii, Cyprinus carpio, Carssus auratus, Clariaslazera, Liza abu. The family Cyprinidae was more diverse than the rest of the families, with a percentage of 40%, and it included two genera to which two species belonged, while the percentage of the rest of the families was 20% for each of them, and each of them included one genusfollowed by one species. The percentage of the species L. abu. 39.82% of the total catch, while T. zillii came second with 27.43%, C.carpio 20.35%, C. lazera 7.07%, and finally C. auratu 5.30%.